A FIRANN as a differential relay for three phase power transformer protection. - Orille-Fernandez, A.L.
This paper presents an application of a finite impulse response artificial neural network (FIRANN) as differential protection for a real three phase power transformer. Three FIRANNs are designed, trained and tested. The first one has an output which identifies internal faults from any other cases like inrush current and external faults. The two others FIRANNs, each have two outputs that classify between internal and external faults, so that a backup protection is included. These FIRANNs have six inputs, one for each sampled current signal from both transformer sides. The sample rate selected is 2 kHz for a 50 Hz power frequency. All FIRANNs were trained to have a 3.5 ms fault detection time, which is considered as a very fast protection. The test results show very good behavior of the FIRANN as a differential protection and it is planned to build a prototype
Keywords: 2 kHz; 3.5 ms; 50 Hz; FIRANN differential relay; Backup protection; Differential protection; Fault detection time; Finite impulse response artificial neural network; Internal fault identification; Three-phase power transformer protection